THE IMPACT PROPHET LEADERSHIP AND ORGANIZATIONAL COMMITMENT ON MOTIVATION AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE OF THE BANK SYARIAH AL SALAAM - Zainuri, Zainuri; Aima, Muhammad Havidz (Dinasti Publisher, 2019)
The purpose of this study is to understand and explain the impact of Prophet Leadership and organizational commitment on motivation and its implications on employee performace of the PT.Bank Syariah Al Salaam. The research method used a quantitative approach, which the population in this study was 80 employees of the Bank Syariah Al Salaam Sample selection was done by sampling technique all population 80 respondents were determined. Data collection techniques using interview and questionnaire. The questionnaire survey instrument was delivered to employees of the Bank Syariah Al Salaam. Data were analyzed by using structural equation model (SEM) with the Smart PLS3.0 software program. This study reveals that Prophet Leadership, organizational commitment and motivation have a significant positive effect on employee performance, both partially and simultaneously. Besides that, the motivation partially mediate variable of the Prophet Leadership variable and organizational commitment on employee performance and has a significant effect